PENGUATAN PEMASARAN IKAN AIR TAWAR BERBASIS ANDROID - Yossie Maria Yulianty Yacob; Yeremias M. Pell; Matheus Dwinanto (Jurnal Abdi Insani, 2023)
The Tunas Baru business unit is a freshwater fish cultivation group in Mata Air Village which still uses conventional fish marketing and sales systems. In this digital era, this method is no longer an effective and efficient way to increase income, so a more effective and efficient Android-based marketing and sales method is needed to increase daily turnover and productivity. The aim of this activity is to disseminate the eFishery application as an Android-based application that can carry out Android-based marketing and sales of freshwater fish. This activity method begins with recognizing partners' need for an Android-based fish marketing and sales application that can increase income. Followed by the formulation of the problems encountered and the unification of ideas to solve these problems. Furthermore, dissemination and application of the eFishery application is carried out for partners in running their business every day. Evaluation of activities is carried out as a final check of all activities that have taken place. The results of this activity show that the use of Android-based marketing and sales applications is very useful for increasing business owners' income both in the short and long term. This application has a good influence on the effectiveness of fish cultivation because it makes it easier for business owners to obtain the latest information that is directly related to the cultivation of various types of freshwater fishery products.